(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Greater core stability provides a foundation for greater force production in the upper and lower extremities. When the core muscles are functioning optimally, the person will be able to safely perform specific athletic or other functional activities. Core muscle imbalances are the cause of core instability and reduced balance performance. Few studies have shown the effect of swiss ball exercises on core stabilization and balance performance as well as few studies also shown the comparison between core exercise on stable and unstable surfaces for core stabilization and balance performance. The core stability and balance performance needs to be treated by strengthening core muscles. Objectives: To find the effect of 2 different types of strengthening exercises on core stability and dynamic balance in collegiate athletes. Material and Method: In this pre-post intervention study 26 athletes were included. They were randomly divided into 2 groups with 13 individuals in each group. Group A was instructed to perform BOSU ball exercises and group B was instructed to perform thera band exercises for 6 weeks. After pre-post assessment, data was analysed with the help of appropriate statistical methods. Results: According to the results there is significant increase in both right and left anterior, posteromedial and posterolateral directions with p value <0.0001 as well as in core stability with p value <0.0001 Conclusion: Both BOSU Ball exercises and thera band exercises are found to be equally effective in improving core stability and balance performance in collegiate athletes